2021
DOI: 10.1186/s12967-021-03178-6
|View full text |Cite
|
Sign up to set email alerts
|

SIRT5 functions as a tumor suppressor in renal cell carcinoma by reversing the Warburg effect

Abstract: Background The aim of this study was to investigate the biological functions and underlying mechanisms of SIRT5 in clear cell renal cell carcinoma (ccRCC). Methods SIRT5 expression data in The Cancer Genome Atlas Kidney Clear Cell Carcinoma (TCGA-KIRC) were selected, and the correlations between SIRT5 expression and various clinicopathological parameters were analysed. SIRT5 expression in ccRCC tissues was examined using immunohistochemistry. Stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Previous research has demonstrated that decreased SIRT5 expression in KIRC accelerated the Warburg effect through PDHA1 hypersuccinylation, resulting in tumorigenesis and progression ( Yihan et al, 2021 ). Here, in KIRC, we found a negative correlation between the expression of PDHA1 and clinical staging by exploring TCGA-KIRC datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that decreased SIRT5 expression in KIRC accelerated the Warburg effect through PDHA1 hypersuccinylation, resulting in tumorigenesis and progression ( Yihan et al, 2021 ). Here, in KIRC, we found a negative correlation between the expression of PDHA1 and clinical staging by exploring TCGA-KIRC datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies suggest that the expression of SIRT5 is decreased in ccRCC and that it can induce tumorigenesis and progression by accelerating the Warburg effect through PDHA1 hyper-succinylation. This indicates that SIRT5 might be a possible ccRCC suppressor ( Yihan et al, 2021 ). Other members in this family were also proven to be important for the tumorigenesis of many cancers.…”
Section: Discussionmentioning
confidence: 97%
“…One study showed that SIRT5 was found to suppress the development of HCC ( Sun et al, 2022 ). In ccRCC, SIRT family members are thought to regulate tumorigenesis, for example, SIRT5 downregulation was thought to promote metabolic reprogramming of ccRCC, the expression of SIRT5 was found to be decreased, and its downregulation can induce tumorigenesis and progression by accelerating the Warburg effect through PDHA1 hyper-succinylation, indicating that this marker might be a possible ccRCC suppressor ( Yihan et al, 2021 ). Although some SIRT members were proven to be important for the development and progression of ccRCC, for example, Tan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Predicted targets of miR-10b among the GPR genes included Fanconi Anemia Complement Group C (FANCC), Kruppel Like Factor 11 (KLF11), SEC14 Like Lipid Binding 2 (SEC14L2), Sirtuin 5 (SIRT5), Sad1 and UNC84 Domain Containing 2 (SUN2), and Tripartite Motif Containing 35 (TRIM35), all of which have been implicated previously in the control of cell proliferation (25,28,31,(45)(46)(47)(48). We measured the expression level of these genes by qPCR after LNA-mediated miR-10b inhibition and observed small but significant changes in KLF11, SIRT5, and SEC14L2; a modest and significant upregulation of FANCC and SUN2; and a robust and significant increase in expression of TRIM35 (~2-fold) (Figure 8D).…”
Section: Jcimentioning
confidence: 99%